Tropicalization of seagrass macrophytodetritus accumulations and associated food webs - Lepoint, Gilles; Hyndes, Glenn A. (Frontiers in Marine Science, 2022)
Seagrass, systems export significant amounts of their primary production as large detritus (i.e. macrophytodetritus). Accumulations of exported macrophytodetritus (AEM) are found in many areas in coastal environment. Dead seagrass leaves are often a dominant component of these accumulations, offering shelter and/or food to numerous organisms. AEM are particular habitats, different from donor habitats (i.e. seagrass meadow, kelp or macroalgae habitats) and with their own characteristics and dynamics. They have received less attention than donor habitats despite the fact they often connect different coastal habitats, are the place of intense remineralization processes and shelter associated detritus food web. As for seagrass meadows themselves, AEM are potentially affected by global change and by tropicalization processes. Here, we review briefly general characteristic of AEM with a focus on Mediterranean Sea and Western Australia and we provide some hypotheses concerning their tropicalization in a near future. We conclude that AEM functioning could change either through: (1) declines in biomass or loss of seagrass directly due to increased ocean temperatures or increased herbivory from tropicalized herbivores; (2) increased degradation and processing of seagrass detritus within seagrass meadows leading to reduced export; (3) replacement of large temperate seagrass species with smaller tropical seagrass species; and/or (4) loss or changes to macroalgae species in neighboring habitats that export detritus. These processes will alter the amount, composition, quality, timing and frequency of inputs of detritus into ecosystems that rely on AEM as trophic subsidies, which will alter the suitability of AEM as habitat and food for invertebrates.